2014
DOI: 10.1177/1532440014534270
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Reexamination of the Effect of Antiabortion Legislation in the Post-Casey Era

Abstract: Michael J. New, in a recent article in this journal, argues that a major reason for the decline in the incidence of abortion since the U.S. Supreme Court's 1992 Casey decision was the increased number of antiabortion laws—parental involvement laws and informed consent laws—enacted at the state level. However, New's analysis contained critical data, measurement, methodological and estimation errors. This article details all the errors and then reexamines the effect of restrictive state abortion laws on the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The primary alternative to the CDC abortion data are from the Guttmacher Institute. Although those data include abortions for all states and are considered to be more reliable (Medoff & Dennis, ), they are only reported periodically and are not publicly available. Further, CDC data have been found to reflect trends observed in the Guttmacher Institute data (Jones & Jerman, ).…”
Section: Empirical Specificationmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary alternative to the CDC abortion data are from the Guttmacher Institute. Although those data include abortions for all states and are considered to be more reliable (Medoff & Dennis, ), they are only reported periodically and are not publicly available. Further, CDC data have been found to reflect trends observed in the Guttmacher Institute data (Jones & Jerman, ).…”
Section: Empirical Specificationmentioning
confidence: 99%
“…New (2011) reassessed the issue and found that Medicaid funding restrictions were associated with a decrease in the abortion rate by 8% to 9 %. Medoff and Dennis (2014) argue that New (2011) misclassifies the presence and timing of the state Medicaid funding restrictions and fails to account for interstate travel among women receiving abortions. However, they too found a decrease in the abortion rate due to the restrictions, ranging from approximately 6% to 9%.…”
Section: Background and Related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Medoff [27,36,37] found that, over the time period 1982-2005, mandatory waiting periods in general and twovisit laws in particular have no effect on the overall incidence of abortion. Similarly, Bitler and Zavodny [7] found that, over the period 1974-1997, mandatory waiting periods had no significant effect on the overall abortion rate, but did increase the percentage of abortions performed after the first trimester of pregnancy.…”
Section: Mandatory Waiting Period Lawsmentioning
confidence: 99%